Evoked potentials in bipolar disorder - review of the literature - Masiak, Jolanta (Current Problems of Psychiatry, 2010)
This publication is the review of the literature on evoked potentials in bipolar disorder. Patients with bipolar disorder (BD) exhibit aberrations in evoked potentials. Increasing number of investigations of evoked potentials in bipolar disorder gave contribution to an effort to discover the endophenotypes for this disorder mesurment of evoked potentials could also be the method of efectivness of the treatments with SSRIs and lithium of bipolar dis-order. Increasing number of investigations of evoked potentials in bipolar disorder gave many important informa-tion and allowed this clinical and neuropsychological data to extrapolate to neurophysiological background al-though currently, no neurophysiological marker exists for bipolar disorder.